Scale and the parable of the ‘dishonest’ steward - McKenzie, Robin (Theology, 2025)
This study of scale in quantities of oil and wheat contracts in Luke 16.1–9 provides an analysis of the size of farm necessary to supply such quantities. It also analyses supply in the main consumer market in Rome, examines scale within the gospel canon, and reappraises the steward’s character.